Identifying resistance in wild and ornamental cherry towards bacterial canker caused by Pseudomonas syringae. (21st December 2021) - Hulin, Michelle T.; Vadillo Dieguez, Andrea; Cossu, Francesca; Lynn, Samantha; Russell, Karen; Neale, Helen C.; Jackson, Robert W.; Arnold, Dawn L.; Mansfield, John W.; Harrison, Richard J.
Abstract: Bacterial canker is a major disease of stone fruits and is a critical limiting factor to sweet cherry ( Prunus avium ) production worldwide. One important strategy for disease control is the development of resistant varieties. Partial varietal resistance in sweet cherry is discernible using shoot or whole tree inoculations; however, these quantitative differences in resistance are not evident in detached leaf assays. To identify novel sources of resistance to canker, we used a rapid leaf pathogenicity test to screen a range of wild cherry, ornamental Prunus species and sweet cherry × ornamental cherry hybrids with the canker pathogens, Pseudomonas syringae pvs syringae, morsprunorum races 1 and 2, and avii . Several Prunus accessions exhibited limited symptom development following inoculation with each of the pathogens, and this resistance extended to 16 P . syringae strains pathogenic on sweet cherry and plum. Resistance was associated with reduced bacterial multiplication after inoculation, a phenotype similar to that of commercial sweet cherry towards nonhost strains of P . syringae . Progeny resulting from a cross of a resistant ornamental species Prunus incisa with susceptible sweet cherry ( P . avium ) exhibited resistance indicating it is an inherited trait. Identification of accessions with resistance to the major bacterial canker pathogens is the first step towards characterizing the underlying genetic mechanisms of resistance and introducing these traits into commercial germplasm. Abstract : This research paper identifies resistance towards Pseudomonas bacterial canker in Prunus species using detached leaf assays.